2007
DOI: 10.1108/09556220710717035
|View full text |Cite
|
Sign up to set email alerts
|

A model for the twist distribution in the slub‐yarn

Abstract: 2016),"Consumers' behavioural intentions after experiencing deception or cognitive dissonance caused by deceptive packaging, package downsizing or slack filling", European Journal of Marketing, Vol. 50 Iss 1/2 pp. 213-235 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…Lu, Gao, and Wang (2007) present a theoretical analysis of slub yarns and conclude that twist should be proportional to 1/(tex) 2 while Johnson and Young (1986) affirm that redistribution should follow the twist factor, i.e. twist should be proportional to 1= ffiffiffiffiffiffi tex p , although they observed a larger dependence.…”
Section: Statistical Analysis Of the Helix Anglementioning
confidence: 94%
“…Lu, Gao, and Wang (2007) present a theoretical analysis of slub yarns and conclude that twist should be proportional to 1/(tex) 2 while Johnson and Young (1986) affirm that redistribution should follow the twist factor, i.e. twist should be proportional to 1= ffiffiffiffiffiffi tex p , although they observed a larger dependence.…”
Section: Statistical Analysis Of the Helix Anglementioning
confidence: 94%
“…Benang slub adalah salah satu benang hias dengan beberapa bagian tebal pada benang (slub) yang dihasilkan melalui perubahan kepadatan linear benang secara sistematis selama proses pemintalan. 11 Dari beberapa penelitian sebelumnya telah diketahui bahwa parameter utama benang slub seperti panjang slub, jarak slub, ketebalan slub, panjang benang dasar, nomor benang, twist, dan lain-lain berpengaruh terhadap kekuatan dan mulur benang. 12,13,14 Dalam literatur lain terdapat beberapa penelitian lain yang menyatakan bahwa beberapa parameter dari benang slub yang digunakan sebagai benang pakan pada kain tenun memiliki efek yang signifikan secara statistik terhadap hasil uji kekuatan arah pakan pada kain tenun.…”
Section: Pendahuluanunclassified
“…[8] Lu et al investigated the influence of yarn twist on the mechanical and physical properties of the slub yarn and concluded that the slub length is a key factor to decide the yarn twist. [9] Some mechanical properties of slub yarn have been analyzed using statistical methods. [4] It has been reported that the twist distribution in every section of slub yarn is inversely proportional to the square of linear density of the corresponding section.…”
Section: Introductionmentioning
confidence: 99%
“…[4] It has been reported that the twist distribution in every section of slub yarn is inversely proportional to the square of linear density of the corresponding section. [9] The parameters of rotor spun slub yarn were investigated and it was found that rotor diameter, yarn count, slub thickness and performance of the servomotor significantly affect the slub length. [10] The important parameters of slub yarn include the slub length, slub distance (pause length/base yarn), mass increase or mass decrease within a slub (slub thickness) or within a pause (pause thickness) and the repetition pattern of the slub yarn as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%